Metric clusters in evolutionary games on scale-free networks - Kaj-Kolja Kleineberg (Nature Portfolio, 2017)
Heterogeneous complex networks tend to be a more realistic representation of social networks than homogenous ones. Here Kleineberg investigates the role of network heterogeneity in the emergence of cooperation in social dilemmas and shows that it can sometimes hinder it.